2003
DOI: 10.1097/00000542-200307000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Bronchodilator Treatment with Intravenous Colforsin Daropate, a Water-soluble Forskolin Derivative, on Airway Resistance after Tracheal Intubation

Abstract: Prophylactic treatment with colforsin daropate produced lower R(awm) and R(awe) and higher C(dyn) after tracheal intubation when compared with placebo medication. Pretreatment before intubation may be beneficial and advantageous for middle-aged smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Clinical trials demonstrated the low toxicity of the water-soluble forskolin in the treatment of patients with cardiac dysfunction or bronchospasm (Wajima et al, 2003;Kikura et al, 2004). Furthermore, the use of forskolin as an antileukaemogenic agent is not unprecedented, as it inhibits growth and/or induces apoptosis of different types of leukaemic cells in vitro (Laneuville et al, 1992;Moon and Lerner, 2003).…”
Section: Adverse Molecular Effects Of Bcr/abl and Pp2amentioning
confidence: 99%
“…Clinical trials demonstrated the low toxicity of the water-soluble forskolin in the treatment of patients with cardiac dysfunction or bronchospasm (Wajima et al, 2003;Kikura et al, 2004). Furthermore, the use of forskolin as an antileukaemogenic agent is not unprecedented, as it inhibits growth and/or induces apoptosis of different types of leukaemic cells in vitro (Laneuville et al, 1992;Moon and Lerner, 2003).…”
Section: Adverse Molecular Effects Of Bcr/abl and Pp2amentioning
confidence: 99%
“…These three respiratory variables were measured and analysed using a CP-100 pulmonary function monitor (Bicore, Irvine, CA, USA) attached to a flow transducer (VarFlex Ò ; Bear Medical Systems, Inc., Palm Springs, CA, USA) and an oesophageal balloon catheter (SmartCath Ò , Bear Medical Systems, Inc.). [10][11][12][13] The arterial blood sample was obtained to measure plasma epinephrine and norepinephrine just before infusion of saline or carperitide (baseline) and 30 min later (just before induction of anaesthesia). The study ended before the start of the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] In addition, we believe any case involving anaesthesia induction with thiamylal and fentanyl and tracheal intubation to be at risk of bronchoconstriction. 13 In the present study, we used this 'model of Ó The Board of Management and Trustees of the British Journal of Anaesthesia 2006. All rights reserved.…”
mentioning
confidence: 99%
“…Oral forskolin performed better than sodium chromoglycate in preventing asthma attacks in children and adults with mild/moderate persistent asthma, whereas inhaled forskolin was similar to beclomethasone in lung function improvement (Bauer et al, 1993; Gonz alez-S anchez et al, 2006; Huerta et al, 2010). Also when administered intravenously, forskolin had a clear bronchodilation effect and no adverse events were described (Wajima et al, 2002(Wajima et al, , 2003.…”
Section: Forskolin As An Old Natural Occurring Camp Elevating Compounmentioning
confidence: 99%
“…As reported above, forskolin (or its water-soluble derivative colforsin) has been tested in several clinical settings including cardiovascular diseases, psychiatric disorders and asthma (Bersudsky et al, 1996;Wajima et al, 2003;Kikura et al, 2004).…”
Section: Forskolin As An Old Natural Occurring Camp Elevating Compounmentioning
confidence: 99%